Postmodern Canadian fiction and the rhetoric of authority - Deer, Glenn (McGill-Queen's University Press, 1994)
Deer illuminates the psychology of family relations and power struggles in Sheila Watson's The Double Hook, the surrealism and spirit of sexual rebellion in Leonard Cohen's Beautiful Losers, the tensions between private psychology and public politics in Dave Godfrey's The New Ancestors, the implied male sympathies in the guise of a feminist persona in Robert Kroetsch's Badlands, the playful yet didactic uses of history in George Bowering's Burning Water, and the paradoxes of power in Margaret Atwood's dystopia, The Handmaid's Tale. Inspired by the philosophies of rhetoric and social discourse in the work of Kenneth Burke, Roger Fowler, Wayne Booth, and George Dillon, Deer forcefully engages the politics of postmodernism in its theoretical and literary dimensions by reading against the grain of canonizing criticism. He provides a detailed discussion of the connections between postmodern literary forms and world views and focuses particularly on how novels are scripted to influence readers and what kinds of world and social views are being promoted. Combining the ethical focus of Wayne Booth and Gerald Graff with elements of deconstruction, Deer's specialized readings of the novels imaginatively construct the addresser-addressee relations of texts and explicate narrative authority. This study will be of particular interest to students of Canadian literature and literary politics as well as scholars of rhetorical theory and criticism.